2018
DOI: 10.1371/journal.pone.0202088
|View full text |Cite
|
Sign up to set email alerts
|

Energy metabolism and partition of lactating Zebu and crossbred Zebu cows in different planes of nutrition

Abstract: The aim of this study was to determine the energy metabolism and partition of lactating Gyr and F1 Holstein x Gyr (F1 HxG) cows in different planes of nutrition. Six F1 HxG and six Gyr cows with 130 days in milking (DIM) fed corn silage and concentrate were evaluated. The experiment consisted of four periods with different levels of feeding: 1st ad libitum dry matter intake (DMI) and the others with 5, 10 and 20% restricted DMI, related to the first one. An apparent digestibility assay was performed before mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
(22 reference statements)
0
9
1
2
Order By: Relevance
“…These BCs are the main basis of the Brazilian dairy herd and research efforts on genetic selection have been showing significant increases in milk production. Due the dual purpose of the Zebu crossbred, they may reach high body condition scores, which can lead to calving problems and future lactation performance [7]. However, our results indicated that Holstein heifers fed at MFL demonstrated a higher FE, which means that the nutrients may be used more efficiently for the basal metabolism and product formation.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…These BCs are the main basis of the Brazilian dairy herd and research efforts on genetic selection have been showing significant increases in milk production. Due the dual purpose of the Zebu crossbred, they may reach high body condition scores, which can lead to calving problems and future lactation performance [7]. However, our results indicated that Holstein heifers fed at MFL demonstrated a higher FE, which means that the nutrients may be used more efficiently for the basal metabolism and product formation.…”
Section: Discussionmentioning
confidence: 65%
“…Data comparing the performance of different BCs of Holstein × Gyr is not consistent due to the large influence of production systems, diet composition, and genetic variation found in tropical countries. Studies using animals with standardized genetics, age, and physiological state is warranted [7,8]. Better performance estimates are crucial for dairy operations to achieve adequate and more predictable animal performance, avoiding inefficient use of nutrients and resources.…”
Section: Introductionmentioning
confidence: 99%
“…The Brazilian dairy herd is composed of approximately 70% of Holstein × Gyr animals [ 9 , 10 ] and this crossbred has greater milk production than the Gyr breed itself. This greater milk production is likely a result of heterosis, which incorporates the best characteristics of each breed; milk production from Holstein and adaptability to tropical climate from Gyr [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Brazilian dairy herd is composed of approximately 70% of Holstein × Gyr animals [ 9 , 10 ] and this crossbred has greater milk production than the Gyr breed itself. This greater milk production is likely a result of heterosis, which incorporates the best characteristics of each breed; milk production from Holstein and adaptability to tropical climate from Gyr [ 10 ]. In a meta-analysis, Oliveira [ 11 ] found lower maintenance requirements and lower efficiency for milk production of crossbred Bos taurus × Bos indicus , compared to Bos taurus breeds.…”
Section: Introductionmentioning
confidence: 99%
“…Las vacas cebuínas y cruzadas Holstein x cebuínas bajo diferentes perfiles de alimentación y nutrición energética restringida mostraron que utilizan la energía a medida que aumenta la producción lechera (Araujo et al, 2018).…”
Section: Requerimientos Energéticos Y Alimentación De La Vaca Lecheraunclassified